Relationship between changes in speed during competitive training period and the participation of soccer players during matches - Volpi Braz, T.; Borin, J. P.; Pagoto Spigolon, L. M.; Cunha, S. A.; Cavaglieri, C. R.; Gomes, A. C. (Brazilian Journal of Biomotricity, 2013)
This study seeks to relate changes in velocity during competitive with the participation of soccer players during matches. Participants were 17 soccer players (16,3 ± 0,4 years, 70,2 ± 6,1 kg, 176 ± 6,4 cm. We evaluated the speed at 10m (V10m) and 30m (V30m) in two separate stages: beginning and end of 17 weeks observed. Descriptive statistics we used measures of centrality and dispersion in inferential, Shapiro-Wilk test to verify the normality of the data, Pearson correlation for the relationship between variables, with p<0,05. The results show strong positive correlation between the percentage of difference between front-end for V10m (r = 0,811, r2 = 0,658, 95% CI = 0,54 to 0,93, p <0,05) and moderately negative for V30m (r = -0,598, r2 = 0,350, 95% CI = -0,84 to -0,17, p<0,05), with the percentage of the volume of competitive soccer team. From this it follows that the greater participation of the players during the matches resulted in the development of variable V10m and decreased for the variable V30m, but the result found for variable V30m probably depends upon the content of training applied and by lower volume of motor actions in the V30m occurs during training with the ball and very competitive activity of soccer players when compared to V10m. Moreover, there was disparity between the training sessions applied to players who did not participate in matches with the stimulus caused by the matches, making it difficult to maintain the organizational structure of training of staff during the competitive season.